Bioluminescence in Clinical and Point-of-Care Testing - Sherwin Reyes; Raymarcos Rodriguez; Emre Dikici; Sylvia Daunert; Sapna Deo (Biosensors)
Point-of-care testing (POCT) offers a transformative approach to diagnostics by enabling rapid and accurate results at or near the site of patient care. This is especially valuable in critical care, emergency settings, and resource-limited areas. However, one major limitation of POCT remains its analytical sensitivity, particularly in detecting low concentrations of analytes. To address this, various innovations are being explored, including advanced sensors, signal amplification, and sensitive labels. Among these, bioluminescent proteins have gained attention for their high sensitivity, fast readout, minimal background interference, and simplified instrumentation. Bioluminescence—light emission from biochemical reactions—presents an ideal platform for enhancing POCT sensitivity. In parallel, metal–organic frameworks (MOFs), especially structures like ZIF-8, are emerging as valuable materials in biosensing. Their high porosity, tunable surface properties, and ability to host biomolecules make them excellent candidates for improving analyte capture and signal transduction. When integrated with bioluminescent systems, MOFs can stabilize proteins, concentrate targets, and enhance overall assay performance. This review highlights the role of bioluminescent proteins in medical diagnostics and their application in POCT platforms. We also discuss the potential synergy between MOFs and bioluminescence to overcome current sensitivity limitations. Finally, we examine existing challenges and strategies to optimize these technologies for robust, field-deployable diagnostic tools. By leveraging both the natural sensitivity of bioluminescence and the structural advantages of MOFs, next-generation POCT systems can achieve superior performance, driving forward diagnostic accessibility and patient care outcomes.